Effect of Stress and Moisture Content on Permeability of Gas-Saturated Raw Coal - Junhui Wang; Zhijun Wan; Yi Wang; Zhixiang Liu; Sifei Liu; Hongwei Zhang; Qiuyan Pei (Geofluids)
Hydraulic fracturing and premining gas drainage are important to safe mining and coalbed methane extraction. These technical processes cause the redistribution of in-situ stress and the regional variation of moisture contents within the affected zone. Therefore, we investigated the coupled effect of variable stresses (from 9 MPa to 27 MPa) and moisture contents (from 0.22% to 4.00%) on the permeability evolution of gas-saturated raw coal. The results show that (1) the relationship between the mean effective stress and the permeability can be described by a power function according to the permeability evolution model of the porous matrix established in this study. Besides, the influence mechanisms of moisture on fitting coefficients in the function were analyzed. (2) The permeability decreases with the increase of in-situ stress (e.g., confining pressure or volumetric stress) in a negative exponential manner. (3) The curves of permeability variations with moisture content are not always linear, and the permeability is more sensitive to the moisture content than the volumetric stress in the test range. Moreover, the sensitivity of permeability varies in different regions. These results would be beneficial for permeability prediction and surface well parameters design.